Lower risk of atopic dermatitis among infants born extremely preterm compared with higher gestational age. (December 2013) - Barbarot, S.; Gras‐Leguen, C.; Colas, H.; Garrot, E.; Darmaun, D.; Larroque, B.; Roze, J.C.; Ancel, P.Y.
Summary Background It is not yet known whether the risk of developing atopic dermatitis (AD) is influenced by preterm birth. Moreover, AD risk has not been assessed in a large sample of extremely preterm infants (< 29 weeks' gestation). Objectives To determine whether the risk of AD is influenced by preterm birth. Methods We investigated the relationship between gestational age (GA) and AD using data from two independent population‐based cohorts, including a total of 2329 preterm infants, of whom 479 were born extremely preterm. Results There was a lower percentage of children with AD in the extremely preterm group compared with those born at a greater GA (Epipage cohort, 2‐year outcome: 13·3% for 24–28 weeks, 17·6% for 29–32 weeks, 21·8% for 33–34 weeks, P = 0·02; LIFT cohort, 5‐year outcome: 11% for 24–28 weeks, 21·5% for 29–32 weeks, 19·6% for 33–34 weeks, P = 0·11). After adjusting for confounding variables, a lower GA (< 29 weeks) was significantly associated with decreased risk of AD in the Epipage cohort [adjusted odds ratio (aOR) 0·57, 95% confidence interval (CI) 0·37–0·87; P = 0·009] and the LIFT cohort (aOR 0·41, 95% CI 0·18–0·90; P = 0·03). Conclusions Very low GA (< 29 weeks) was associated with a lower risk of AD compared with higher GA (29–34 weeks) and full‐term birth.